Phenacoccus solani Ferris (Homoptera Coccoidea) on ornamental plants in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
A new record in Italy of the mealybug Phenacoccus solani Ferris(Homoptera Coccoidea) on Encephalartos sp. (Cycadaceae) in cold greenhouseis reported together with some morphological comments.
Keywords: Cycadaceae; morphology; scale insects; Sicily